Considerations on Visitor Satisfaction as Part of an Integral Evaluation Methodology - Bazán, Liliana Natalia (2021)
This research article presents the application of a model of museum visitors' satis-faction which was developed through visitor studies in four museums in Argentina. The model aimed to identify what influence the visitors' own characteristics, as well as their perception of the experience the museum offers them, had on their overall satisfaction. Data was collected in two stages: one before the visit and another one immediately after. This process permitted the identification of certain common pat-terns to all the case studies in relation to visitors' satisfaction, a necessary condition to better understand their needs and behavior, in order to generate memorable experiences.